Caminoisation and Cathedrals: replication, the heritagisation of religion, and the spiritualisation of heritage. Issue 1 (2nd January 2019) - Bowman, Marion; Sepp, Tiina
ABSTRACT: This article focuses upon a specific aspect of the revival of pilgrimage in Europe, the replication of the Camino de Santiago. The Camino has become regarded increasingly as 'prototypical' pilgrimage, particularly by those previously largely unfamiliar with pilgrimage, and copied in contexts far from Spain. This tendency towards the importation, re-conceptualisation and (to varying degrees) replication of the Camino in the pilgrims' native countries has led to the revival of ancient pilgrimage routes as well as the development of new ones. 'Caminoisation' thus refers to the process of introducing aspects of the Camino pilgrimage to other routes and pilgrimage sites. Among the main features of Caminoisation are the ideas that 'real' pilgrimage is done on foot and that the journey is more important than the destination. In addition, the material culture of the Camino is spreading, including pilgrim passports and Compostela-like certificates, as are ritual activities such as pilgrim blessings. Based on our AHRC funded project on Pilgrimage and England's Cathedrals, Past and Present, (PEC) we examine the growth and variety of pilgrimage activities in the post-Reformation, Anglican contexts of Canterbury Cathedral, York Minster and Durham Cathedral. We explore the renegotiation of pilgrimage, the localisation of Camino features in traditionally Protestant contexts and the implications of Caminoisation for the Anglican Cathedrals studied within the broader milieu of the heritagisation of religion and the spiritualisation of heritage in Europe.